Event Study of Announcement Impacts on Redirecting Fuel Subsidies towards Sharia Stock Performance - Siti Amaroh; Husnurrosyidah Husnurrosyidah; Badingatus Solikhah (Ekonomi Syariah IAIN Kudus, 2023)
This study aims to examine if there is a difference in the average abnormal return and trading volume of Sharia shares listed on the Jakarta Islamic Index before and after the announcement of the diversion fuel subsidy on September 3, 2022. The study was conducted on a sample of 30 company issuers of Sharia shares with an observation period of 10 days before and after the release of a public announcement. The data was analyzed using both the paired sample t-test and the Wilcoxon Signed Rank Test, taking into consideration the normality of the data. The results show that the announcement of diversion subsidies for fossil fuels does not lead to significant changes in the average abnormal returns before and after the announcement. Meanwhile, the Average Trading Volume Activity displays discrepancies before and after the release. This result implies that investors are not responsive to changes in the price of fossil fuels and instead opt to wait before making the decision to either buy or sell shares in the Sharia trade.